Pengembangan Bahan Ajar Berbasis Pembelajaran Interaktif pada Siswa Kelas 4A dan 4C SDPN 252 Setiabudhi - Arwyn Muhammad Sya’bani; Muhammad Maulid Aufa Putra Soejana; Muhammad Salman Naufal; Syauqi Al-Harits Gymnastiar (Lembaga Pengembangan Kinerja Dosen, 2024)
This research focuses on the development of interactive learning materials to enhance the understanding of fourth-grade elementary school students regarding rounding. Pre-tests and post-tests were conducted on the experimental group to measure its effectiveness. The objectives of this study are (1) to develop teaching materials using a clothing measuring tape and (2) to analyze the differences in learning outcomes between students using this media and conventional methods in the 4A and 4C classes at SDPN 252 Setiabudhi. The data analysis activities involve processing the data and applying statistical analysis. The results indicate a lack of significant improvement in students' understanding of rounding concepts after the implementation of interactive teaching materials. Statistical analysis shows that the average scores on the post-test did not exhibit a significant increase compared to the pre-test. In conclusion, the teaching method using a clothing measuring tape is less effective when applied to 4A and 4C students at SDPN 252 Setiabudhi.